(untitled) (Revista Brasileira de Contabilidade e Gestão, 2019)
The present study aims to analyze how third year high school students make up their mind in favor of a given higher education institution. 26 students were interviewed, on a previously prepared script containing the following dimensions: reference groups, brand, government incentive programs, infrastructure and price. Reference groups showed to be the main influence received from students in their choice of IES there seems to be consensus that perception of the brand arises chiefly from experiences shared with relatives and close friends. At this point, a consensus seems to close in upon the ’quality of the institution’, molded by word of mouth. Moreover, the article makes room for questioning about what students would regard as quality of education, considering the intangibility of this service and the difficulty for the student public to assess relevant aspects of what would be a structure that offers quality services. Paramount as a managerial implication is that the HEIs form a brand identity that can be recognized by the community of interest.